Dynamic Balance During Walking in Transfemoral Prosthesis Users: Step-to-Step Changes in Whole-Body and Segment Angular Momenta - Genki Hisano; Hiroto Murata; Toshiki Kobayashi; Matthew J. Major; Motomu Nakashima; Hiroaki Hobara (IEEE Transactions on Neural Systems and Rehabilitation Engineering, 2023)
Transfemoral prosthesis users (TFPUs) typically have a high risk of balance loss and falling. Whole-body angular momentum ( ${\overrightarrow {H}}_{{\text {WB}}}{)}$ is a common measure for assessing dynamic balance during human walking. However, little is known about how unilateral TFPUs maintain this dynamic balance through segment-to-segment cancellation strategies. Better understanding of the underlying mechanisms of dynamic balance control in TFPUs is required to improve gait safety. Thus, this study aimed to evaluate dynamic balance in unilateral TFPUs during walking at a self-selected constant speed. Fourteen unilateral TFPUs and fourteen matched controls performed level-ground walking at a comfortable speed on a straight, 10-m-long walkway. In the sagittal plane, the TFPUs had a greater and smaller range of $\overrightarrow {H}_{{\text {WB}}}$ compared to controls during intact and prosthetic steps, respectively. Further, the TFPUs generated greater average positive and negative $\overrightarrow {H}_{{\text {WB}}}$ than did the controls during intact and prosthetic steps, respectively, which may necessitate larger step-to-step postural changes in the forward and backward rotation about the body center of mass (COM). In the transverse plane, no significant difference was observed in the range of $\overrightarrow {H}_{{\text {WB}}}$ between groups. However, the TFPUs displayed smaller negative average $\overrightarrow {H}_{{\text {WB}}}$ in the transverse plane than did the controls. In the frontal plane, the TFPUs and controls demonstrated similar range of $\overrightarrow {H}_{{\text {WB}}}$ and step-to-step whole-body dynamic balance owing to the employment of different segment-to-segment cancellation strategies. Our findings should be interpreted and generalized with caution for the demographic features in our participants.